Outdoor lighting for pedestrians : a guide for safe and walkable places - Markowitz, Frank (Routledge, 2022)
"Outdoor Lighting for Pedestrians shows how outdoor lighting is important for pedestrians' safety, personal security, and comfort, with major impacts on street, path, and park aesthetics and neighborhood sense of place. Providing clear, basic technical background (accessible to non-engineers), the book focuses especially on planning and policy concerns. It covers the fundamentals of lighting technology; benefits, costs, and possible adverse impacts of lighting enhancements; traditional and innovative approaches; planning and policy documents and practices; aesthetics and placemaking; and technology trends in lighting design. This book is aimed primarily at practicing transportation planners and engineers, generalist urban planners, safety advocates and researchers, and university students. However, lighting designers and other professionals will also find it useful. It considers how lighting can be coordinated with other potential improvements to enhance the pedestrian environment for better walkability"--